"I wouldn't know where to start": Perspectives from clinicians, agency leaders, and autistic adults on improving community mental health services for autistic adults. (May 2020) - Maddox, Brenna B; Crabbe, Samantha; Beidas, Rinad S; Brookman-Frazee, Lauren; Cannuscio, Carolyn C; Miller, Judith S; Nicolaidis, Christina; Mandell, David S
Most autistic adults struggle with mental health problems, and traditional mental health services generally do not meet their needs. This study used qualitative methods to identify ways to improve community mental health services for autistic adults for treatment of their co-occurring psychiatric conditions. We conducted semistructured, open-ended interviews with 22 autistic adults with mental healthcare experience, 44 community mental health clinicians, and 11 community mental health agency leaders in the United States. The participants identified clinician-, client-, and systems-level barriers and facilitators to providing quality mental healthcare to autistic adults. Across all three stakeholder groups, most of the reported barriers involved clinicians' limited knowledge, lack of experience, poor competence, and low confidence working with autistic adults. All three groups also discussed the disconnect between the community mental health and developmental disabilities systems, which can result in autistic adults being turned away from services when they contact the mental health division and disclose their autism diagnosis during the intake process. Further efforts are needed to train clinicians to work more effectively with autistic adults and to increase coordination between the mental health and developmental disabilities systems. Lay Abstract: Most autistic adults struggle with mental health problems, such as anxiety and depression. However, they often have trouble finding effective mental health treatment in their community. The goal of this study was to identify ways to improve community mental health services for autistic adults. We interviewed 22 autistic adults with mental healthcare experience, 44 community mental health clinicians (outpatient therapists, case managers, and intake coordinators), and 11 community mental health agency leaders in the United States. Our participants identified a variety of barriers to providing quality mental healthcare to autistic adults. Across all three groups, most of the reported barriers involved clinicians' limited knowledge, lack of experience, poor competence, and low confidence working with autistic adults. All three groups also discussed the disconnect between the community mental health and developmental disabilities systems and the need to improve communication between these two systems. Further efforts are needed to train clinicians and provide follow-up consultation to work more effectively with autistic adults. A common suggestion from all three groups was to include autistic adults in creating and delivering the clinician training. The autistic participants provided concrete recommendations for clinicians, such as consider sensory issues, slow the pace, incorporate special interests, use direct language, and set clear expectations. Our findings also highlight a need for community education about co-occurring psychiatric conditions with autism and available treatments, in order to increase awareness about treatment options.